Agamben on secularization as a signature - Voogt, Ariën (International journal of philosophy and theology, 2022)
This article reconstructs Agamben’s contribution to the secularization debate. To this aim it clarifies Agamben’s determination of the category of secularization as a signature. It first presents the relevant passages on secularization from across Agamben’s corpus, placing them in the context of the classic secularization debate between Blumenberg, Schmitt and Löwith. Second, it elaborates on Agamben’s theory of the signature. Third, it proposes how we can understand secularization as a signature. Fourth, it examines the different strategic functions of secularization and profanation in Agamben’s critical philosophy. The article argues that Agamben’s account of secularization comprises two distinct levels. Agamben develops a general theory of secularization as a signature, which implies that it is an operator that orients hermeneutic understanding by referring secular elements to the discursive field of religion and theology (or vice versa), and that always performs a strategic function. To what strategic function Agamben puts secularization to use himself, corresponds to the second, particular level of Agamben’s understanding of secularization. Secularization is in Agamben’s critical project subservient to the operation of profanation. The article is in light of the secularization debate most concerned with the general level of Agamben’s account of secularization.